Exploratory survey in the Atlantic Zone of Costa Rica: contribution of the land group - Kloosterman, H.; Slijkhuis, J.S.A.; Wielemaker, W.G. (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), Turrialba (Costa Rica) Agricultural University Wageningen, Wageningen (Países Bajos) Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
2 mapas. 14 ref.